PENGARUH KOMPETENSI SOSIAL GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) KELAS XI DI SMA NEGERI 3 BONE - A. Mustika Abidin (Jurnal Teknologi Pendidikan Madrasah, 2023)
This study uses an ex-post facto research approach. The results showed that: 1) The social competence of class XI PAI teachers at SMA Negeri 3 Bone has a high level of social competence, namely by having an inclusive attitude, acting objectively, and not discriminating based on gender, religion, race, physical condition, family background , and socioeconomic status; have an adaptive attitude to the socio-cultural environment in which they work; and have a communicative attitude with the teacher community, school residents and community members, 2) The learning motivation of students in Islamic education class XI at SMA Negeri 3 Bone has a high level of learning motivation, namely by having intrinsic motivation (motivation from within the students) and extrinsic motivation (external motivation) on Islamic Religious Education (PAI) lessons. 3) There is an influence of teacher social competence on students' learning motivation in Islamic Religious Education (PAI) class XI at SMA Negeri 3 Bone. This study has succeeded in testing that there is an influence of teacher social competence on students' learning motivation in class XI Islamic Religious Education (PAI) subjects at SMA Negeri 3 Bone. Thus, the implications of this research are that both in the learning process and outside the learning process, teachers are expected to always have social competence so that it influences student learning motivation.